Utilizing a regulated targeted integration cell line development approach to systematically investigate what makes an antibody difficult to express. (10th January 2019) - Tadauchi, Tomofumi; Lam, Cynthia; Liu, Laura; Zhou, Yizhou; Tang, Danming; Louie, Salina; Snedecor, Brad; Misaghi, Shahram
Abstract : Chinese hamster ovary (CHO) cells are conventionally used to generate therapeutic cell lines via random integration (RI), where desired transgenes are stably integrated into the genome. Targeted integration (TI) approaches, which involve integration of a transgene into a specific locus in the genome, are increasingly utilized for CHO cell line development (CLD) in recent years. None of these CLD approaches, however, are suitable for expression of toxic or difficult‐to‐express molecules, or for determining the underlying causes for poor expression of some molecules. Here we introduce a regulated target integration (RTI) system, where the desired transgene is integrated into a specific locus and transcribed under a regulated promoter. This system was used to determine the underlying causes of low protein expression for a difficult‐to‐express antibody (mAb‐A). Interestingly, we observed that both antibody heavy chain (HC) and light chain (LC) subunits of mAb‐A independently contributed to its low expression. Analysis of RTI cell lines also revealed that while mAb‐A LC triggered accumulation of intracellular BiP, its HC displayed impaired degradation and clearance. RTI pools, generated by swapping the WT or point‐mutant versions of difficult‐to‐express antibody HC and LC with that of an average antibody, were instrumental in understanding the contribution of HC and LC subunits to the overall antibody expression. The ability to selectively turn off the expression of a target transgene in an RTI system could help to directly link expression of a transgene to an observed adverse effect. © 2018 American Institute of Chemical Engineers Biotechnol. Prog ., 35: e2772, 2019.